A review: potential of Durio Zibethinus L. (Durian) waste - Shamin-Shazwan, Kamaruddin; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Md Zin, Noor Hasniza (Zibeline International Publishing, 2022)
The fresh arils of durian fruits contained approximately one-third of the fruit's total weight; the remainder of the fruit, including the rinds and seeds, is considered waste. As a result, researchers investigated and studied the potential for these wastes to be processed into products or value-added products in various industries. This review aimed to discuss the potential for waste products of D. zibethinus to be converted into value- added products in a variety of areas. An extensive literature study was done on various search engines. Related previous research was selected for discovering the potential of D. zibethinus waste. This review found four fields of studies that gained interest in the invention of value-added products by using D. zibethinus waste, including activated carbon precursor, bio-composite product, bio-based polymer product, and bioethanol production. As Malaysia is growing in the food waste industry, more study needs to be done to successfully invent new value-added products from D. zibethinus waste such as rind and seed. The effort of this study could help in reducing unused D. zibethinus waste.